ANALISIS PENGARUH BRAND EQUITY TERHADAP PROSES KEPUTUSAN PEMBELIAN PADA KONSUMEN POND’S DI KOTA SURABAYA - IRWANTI, IKA (Universitas Katolik Widya Mandala Surabaya, 2013)
This study aimed to analyze the effect of brand equity on consumer buying decision process on Pond's in the city of Surabaya, and to investigate the respondents' assessment of the brand equity and consumer purchasing decisions on the Pond's facial care products in Surabaya. The sampling technique used in this study was non-probability sampling technique. Sampel of the respondents in this study were women aged 20 to > 50 years who live in the city of Surabaya and use Pond's during the last six months. Data analysis techniques used in this study is structural equation model (SEM). Result of this study indicates that there is has a positive significant effect on Brand Equity on consumer buying decision process. Besides it found that Brand Loyalty is the most powerfull indicator in shaping the Brand Equity and consumer buying decisions is the most powerfull indicator in explaining the buying decision process.